Factors predicting six-month exclusive breastfeeding among mothers in Ho Chi Minh City, Vietnam - Nhan Thi Nguyen (2022)
Purpose: Exclusive breastfeeding (EBF) rates continue to be low in Vietnam. This study aimed to determine the factors predicting 6-month EBF among mothers in Ho Chi Minh City, Vietnam. Design/methodology/approach: A cross-sectional study was conducted with 259 mothers of infants aged between six to nine months at well-baby clinics in Ho Chi Minh City. The questionnaires used for data collection included personal background questionnaire, perceived benefits of breastfeeding scale, breastfeeding self-efficacy scale-short form, perceived barriers to breastfeeding scale and the family support of breastfeeding scale. Descriptive statistics, bivariate and multiple logistic regression were used for data analysis. Findings: About 32% of the Vietnamese mothers practiced 6-month EBF. By increasing one unit of perceived benefits of breastfeeding, perceived self-efficacy in breastfeeding and family support, the mothers' likelihood to give 6-month EBF would increase 19% (AOR = 1.19, 95% CI = 1.08, 1.31), 12% (AOR = 1.12, 95% CI = 1.04, 1.19) and 10% (AOR = 1.10, 95% CI = 1.04, 1.16), while previous breastfeeding experience, maternal age and maternal education could not significantly contribute to the 6-month EBF. Originality/value: This is the first study in Vietnam using a nursing model, the health promotion model, as a framework to identify factors predicting 6-month EBF. An effective program for promoting EBF could be developed by manipulating and tailoring the predicting factors to fit the Vietnamese mothers' needs through a mother class, lactation clinic or individual approach.